National Medicine Examination in Peru 2008-2009: Analysis and Sustainability of Results - Cieza Zevallos, Javier Antonio (2010)
Objective: To assess the consistency of the results of the National Medicine Exam (NME) in Peru for years 2008 and 2009.   Material and method: We examined consistency between general and partial results obtained by the different public and private medical schools from Lima or other cities using official published data regarding the results of NME in Peru for years 2008 and 2009. These results were analyzed taking into account both numerical scores and ordinal variables (when considering the order on the basis of partial results that resulted in the final rank order). Statistical significance was established in p<0.05.   Results: The correlation was good (r>0.90) between the order considering the overall score and rank order in the two periods studied, but the best result was obtained in 2008. The correlation between the rank order obtained in both years was low, with a statistically significant result (r=0.69, p<0.001). The consistency of partial results from universities between 2008 and 2009 was non-existent except in the pediatrics area. The results were different in terms of coming from a public or a private university (both in the overall score and in the medicine area) and being based in Lima or another city (for obstetrics and gynecology and public health items). The model consisting in being a public medical school based in Lima showed a different behavior compared to other variable combinations.   Conclusion: NME results in years 2008 and 2009 showed poor consistency. The results showed a different behavior of public Lima/based medical schools compared with other variable combinations.